Quantitative computed tomography coronary angiography in patients with acute myocardial infarction: association with cardiac biomarkers - A. S. Dasheeva; D. A. Vorobyeva; T. E. Suslova; A. N. Maltseva; A. V. Mochula; V. V. Ryabov; O. V. Mochula; K. V. Zavadovsky (Российский кардиологический журнал)
Aim. To study quantitative parameters of coronary atherosclerosis, according to computed tomography coronary angiography (CTCA), and to identify their association with the level of cardiac biomarkers in patients with acute myocardial infarction (MI).Material and methods. The study included patients with newly diagnosed MI. Depending on the coronary artery (CA) stenosis, two groups were formed: 1) MI with obstructive CA ≥50% (MICAD); 2) MI with non-obstructive CA <50% (MINOCA). All patients were assessed for cardiac biomarkers and underwent CTCA.Results. The study included 31 patients as follows: MINOCA group consisted of 10 patients (5 men aged 68 (57; 79) years); MICAD group — 21 patients (13 men aged 62 (56; 68) years). When analyzing cardiac biomarker levels, a significant increase in cardiac troponin I (cTnI) levels was noted on the 4th (p=0,04) and on the 7th day (p=0,0009) in MICAD patients. A significant predominance of the volume (p=0,01) and burden (p=0,004) of low-density plaques was revealed in the MICAD group compared to MINOCA. In addition, MICAD patients had significantly increased values of the total atherosclerotic burden (p=0,01) and the total burden of the soft tissue component of plaques (p=0,04). A significant correlation was found between the plaque volume with cTnI on day 7 (ρ=0,52, p<0,05) and the plaque burden with cTnI on day 7 (ρ=0,43, p<0,05).Conclusion. According to CTCA, the soft tissue component of plaques is associated with coronary atherosclerosis severity and myocardial damage in patients with MI. Soft tissue burden is a predictor of more severe myocardial damage, according to the cardiac biomarker data.